Bovine Biofertilizer and Water Regime Effects on Growth and Bulb Quality of Garlic - Galbiatti, Joao Antonio [UNESP]; de Nobile, Fabio Olivieri [UNESP]; Fachini, Emerson [UNESP]; Herbert, Italo; Cavalcante, Lucena; Beckmann-Cavalcante, Markilla Zunete; Tarle Pissarra, Teresa Cristina [UNESP] (Taylor & Francis Ltd, 2011)
Garlic is an important vegetable crop, and irrigation and fertilizing are the main factors assuring good production and quality. An experiment was carried out to study growth and bulb physical quality of a garlic crop fertilized with mineral fertilizers and two doses of bovine biofertilizer together with two irrigation regimes. The experiment was a completely randomized design with treatments distributed in a factorial array (2 x 2 x 2) including two water amounts (100 and 50% of recommended irrigation), two biofertilizer doses (20000 and 40000 1 ha(-1) and two application times of biofertilizer (1 and 15 days before sowing). Four control treatments were also included; with and without mineral fertilization with NPK under 50 and 100% of crop recommended irrigation. Height was greater in plants that received more water, for both fertilized and non-fertilized treatments. Application of 40000 1 ha(-1) of bovine biofertilizer at 15 days before sowing substituted for the mineral fertilizing of the garlic crop. Plant irrigation, following technical recommendations is essential for garlic growth and quality production.